2023
DOI: 10.1039/d3ay00654a
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical microfluidic device for non-enzymatic cholesterol determination using a lab-made disposable electrode

Abstract: Cholesterol is an important steroid and hormone precursor, and its level in blood is associated with risk factors for cardiovascular diseases. In this work, a non-enzymatic methodology for cholesterol determination...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…There are also a group of researchers who successfully quantified cholesterol without derivatization from wide range of samples which includes eggs, milk, vegetable oil, human serum and Korean dishes [ [9] , [10] , [11] , [13] , [18] , [19] ]. Among them Choong et al reported high level of cholesterol (193.4–3166.1 μg/g) in vegetable oil which may be the result of overestimation [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also a group of researchers who successfully quantified cholesterol without derivatization from wide range of samples which includes eggs, milk, vegetable oil, human serum and Korean dishes [ [9] , [10] , [11] , [13] , [18] , [19] ]. Among them Choong et al reported high level of cholesterol (193.4–3166.1 μg/g) in vegetable oil which may be the result of overestimation [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been employed to analyze cholesterol, including gravimetry, colorimetry, fluorimetry, and chromatography [ 2 , [7] , [8] , [9] ]. Among these, gas chromatography is considered the most suitable and reliable method to analyzecholesterol, as it allows for the separation of cholesterol from other similar phytosterol compounds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations